The Effectiveness of Dialogical Patrols by the Samapta Patrol Unit in Preventing Theft with Aggravating Circumstances to Maintain Public Security (Kamtibmas) in the Magetan Police - Riva’i, Asyril (Advances in Police Science Research Journal, 2024)
The case of aggravated theft became a criminal offense case with the highest number of reports in 2022-2023 in the Magetan Police jurisdiction. This study aims to evaluate the effectiveness of dialogic patrols in preventing aggravated theft in order to realize Kamtibmas in Magetan Police Station. This research was conducted using field research with a qualitative approach. Data were collected through observation, interviews, and documentation studies. The author tries to examine the implementation of patrol activities, explore the factors that influence it and conclude the effectiveness of this activity. So that the expected output is the discovery of suggestions and input for leaders to evaluate, so that Kamtibmas can be guaranteed.